Heat transport processes of the Indonesian Throughflow along the outflow pathway in the eastern Indian Ocean during the last 160 kyr - Ding, Xuan; Bassinot, Franck; Pang, Xiaolei; Kou, Yingxin; Zhou, Liping (Paleoceanography and Paleoclimatology, 2023)
International audience Abstract As the only low‐latitude connection along the return branch of the Great Conveyor Belt, the Indonesian Throughflow (ITF) plays an important role in the large‐scale ocean–atmosphere interaction in the tropical region. However, the heat transport processes of the ITF along the outflow pathway in the eastern Indian Ocean over the recent geologic period is still debated. In this study, by using Mg/Ca ratios of the surface‐dwelling and thermocline‐dwelling planktonic foraminifera Globigerinoides ruber and Pulleniatina obliquiloculata , we reconstruct surface and thermocline water temperatures and thermocline structure at two sites in the main outflow path of the ITF in the eastern Indian Ocean for the last 160 kyr, and compare these new data with those from two cores in the central Indo‐Pacific Warm Pool. Our results show that, on the orbital time scale, the thermocline structure changes above the equatorial 90°E Ridge mimic those of the eastern Timor Sea, indicating that the ITF vertical structure remained unchanged during its penetration into the Indian Ocean. The thermocline water temperature in the equatorial western Pacific and eastern Indian Ocean presents similar change trend, suggesting that ITF is likely to be an important route for thermocline water transport into the Indian Ocean. However, the vertical structure of the ITF varied through time, reflecting the effects of sea level and orbitally‐driven monsoonal activity. This impacted heat transport processes, resulting in changes in the surface water temperature along the outflow pathway in the eastern Indian Ocean. This article is protected by copyright. All rights reserved.